Experimental and theoretical investigation on degradation of enoxacin in aqueous solution by UV-activated persulfate: Kinetics, influencing factors and degradation pathways. Issue 6 (December 2021) - Zeng, Xiaolan; Meng, Yu; Sun, Xiaozi; Guo, Fang; Yang, Mi
Abstract: In this work, the degradation behavior of enoxacin (ENO) in aqueous solution by UV-activated persulfate (PS) was investigated, and the mechanism for aqueous ENO degradation initiated by sulfate (SO4 − ) and hydroxyl radicals ( OH) was explored by performing density functional theory (DFT) calculation. Under the optimal condition ([ENO]0 = 0.0312 mM, [PS]0 = 1.560 mM, pH0 = 7.0), nearly complete removal of ENO was achieved after 12 min of degradation. The degradation of ENO in the UV/PS system followed pseudo-first-order kinetic model, and the corresponding rate constants increased with increasing PS dosage and decreasing solution pH. The presence of CO3 2− or HCO3 − had an obvious inhibitory effect on ENO degradation. OH contributed mainly to ENO degradation in the UV/PS system. The experimental results for intermediate identification suggested that ENO mainly undergo piperazine ring cleavage in the early stage of degradation, which can be well explained by the theoretical calculation. The computational results also indicated that the electron transfer reactions between ENO and SO4 − ( OH) proceeded hardly both thermodynamically and kinetically. Furthermore, SO4 − was found to be more reactive than OH in degrading ENO. The effective degradation of ENO by UV/PS process suggested that it can be used as an efficient technology to treat ENO-containing water and wastewater. Graphical Abstract: ga1 Highlights: Both experimental and theoretical investigations for ENO degradation were conducted. Effective aqueous degradation of ENO was achieved in UV/PS process. Acidic and neutral condition were more favorable for UV/PS degradation of ENO. Piperazine ring cleavage was the main pathway for ENO degradation involving OH (SO4 − ).